La alimentación y el proceso de aprendizaje. - Bonifaz Yugcha, Eddy Rolando (2018)
This research is aimed at making a preliminary diagnosis about food incidence in the learning process at “Province of Cañar” Elementary School. All of them started from preliminary analyses that led to difficulties or problems existence that children had to carry out the learning process, causing a low academic performance in them. The main objective was to reach the students and parents with the necessary informational content about food incidence and the importance that should be given to food theme in children, and to raise awareness of the advantages and disadvantages that may arise due to food in which there is a learning process. Research is important talking into account that it is evident that students have difficulties during the learning process because they have flaws in their diet and cause knowledge taught by the teacher is not internalized by learners because they do not have the highlighting information feeding importance in children during the learning process and the impact it cause if they do not become aware of food provided to learners. The beneficiaries of this research are students from “Province of Cañar”, Elementary School, in addition to the parents and teacher. In this research elaboration, a suitable methodology is taken into account that allows to obtain necessary contents for its sustenance; for this consider the quantitative paradigm, the quantitative approach that allows us to work taking into account the need for preliminary data in relation to the variables; as a research technique, the survey was applied through a questionnaire as an instrument for the collection of truthful information about the food importance in the learning process. Being a research for the educational area does not cause any impact.